Degree in Nursing: education through problem-based learning - Maria Zilma dos Santos; Márcia Aparecida Padovan Otani; Silvia Franco da Rocha Tonhom; Maria José Sanches Marin
ABSTRACT Objective: To describe how undergraduate courses in Nursing are using the problem-based learning (PBL). Method: Integrative literature review, from searches in the databases Education Resources Information Center (ERIC), Latin American and Caribbean Health Sciences Literature (Lilacs), and PubMed, from 2010 to 2015. 36 articles were analyzed. Results: A teaching method used in all continents, the PBL enables improvement of the critical thinking, autonomy, motivation for learning, active search attitude, ability to work in teams, and problem-solving. Difficulties and challenges relate to the training of students and teachers to understand the principles of the method. Final considerations: The benefits of PBL coincide with the needs of nursing training, but its applicability demands constant review in seeking to develop the skills necessary for this training.